1995
DOI: 10.12693/aphyspola.88.489
|View full text |Cite
|
Sign up to set email alerts
|

On Phonon Dispersion in Alkali Metals

Abstract: In the present paper, the calculatioii of the phonon dispersioii relations for alkali metals to second order in a local pseudopotential is discussed in terms of the real-space sum. Dicherent forms of dielectric functions are employed to judge the varying echects of exchange and correlation on the phonon frequencies. The quantitative agreement of phonon frequencies for the alkali metals reflects, satisfactorily, the experimental trend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Instead of using Vegard's law to obtain screened pseudopotential V (X) for binary mixture, we employed more successful approach of PAA model. 24,[33][34][35][36][37] The form factor V (q) used for the PAA model is (in a.u.) from our recent work.…”
Section: Methods Of Computationmentioning
confidence: 99%
“…Instead of using Vegard's law to obtain screened pseudopotential V (X) for binary mixture, we employed more successful approach of PAA model. 24,[33][34][35][36][37] The form factor V (q) used for the PAA model is (in a.u.) from our recent work.…”
Section: Methods Of Computationmentioning
confidence: 99%
“…The attempts to study the phonon dispersion curves of liquid metals using the pseudopotential theory are very rare and not exhaustive [1][2][3]. Srivastava [1] and Gajjar et al [3] have reported the phonon dispersion of some simple liquid metals.…”
Section: Introductionmentioning
confidence: 99%
“…Srivastava [1] and Gajjar et al [3] have reported the phonon dispersion of some simple liquid metals. It was found that the maximum deviation takes place in the vicinity of the first spherical Brillouin zone.…”
Section: Introductionmentioning
confidence: 99%
“…But it is well established that pseudo-alloy-atom (PAA) is a more meaningful approach to explain such kind of interactions in binary systems. [4][5][6]13,14,17,18 Hence, in the present article, we have adopted PAA model to investigate the SSP of forty binary metallic glasses system.…”
Section: Introductionmentioning
confidence: 99%